Labiritni metropolitani. Sottosuoli politici tra Benjamin e Bataille - Massimo Palma (Kaiak, 2014)
The relationship between Walter Benjamin and Georges Bataille is certainly one, whose relevance has already been stressed from a biographical point of view, the latter being responsible for the conservation of Benjamin’s manuscripts. On the other hand, the purely philosophical-political connection between the two of them is yet to be clarified, since Benjamin’s famous statement on Bataille’s activity, “Vous travaillez pour le fascisme”, can hardly be taken for granted and verified. It is true that in the late Thirties, Bataille and Benjamin do show common subjects, such as the interest for the labyrinth as a social metaphor of the city and of the life of goods where the flâneur feels strangely at ease. Nevertheless, it is true that some among Bataille’s (and Roger Caillois’) solutions cause Benjamin’s reproaches and philosophical mistrust, because of its sterile repetition of subjective heroism as a way out.